The Influence of Creative Gymnastics Exercise on Improving Physical Fitness In Women In Coastal Area Jorong Tanah Laut District - Mita Erliana; Perdinanto; Yanda Hartati; Rabiatul Mirati (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The purpose of this study was to determine the effect of creative gymnastic exercises on women on the coast of Jorong, Tanah Laut. The method used in this study is the pre-experimental method. The population in this study were female traders on the coast of Jorong, totaling 30 people and a sample of 30 people. In this study, a total sampling technique was used, namely the entire population was used as the main sample. The process of carrying out the research was by making creative exercise videos, then the exercises were tested on women on the coast. after the gymnastic movements can be carried out properly and correctly, the researcher provides a creative gymnastic training program 3 times a week, this activity lasts for 2 months.Based on the results of calculations using the t-test, it can be seen that the tcount before exercise with creative gymnastics with aerobic gymnastics is -7.071 with a probability of 0.000, because probability <0.05, it can be concluded that there is a significant effect of creative gymnastics training on increasing fitness body for women along the coast of Jorong, Tanah Laut Regency.